Optimizing Stunting Prevention and Handling Programs in Sinjai Regency - Syamsuddin, Syamsuddin; Nawir, Adi; Aini, Rini Nurul (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2025)
The problem of stunting is still a serious challenge in public health development in Indonesia, especially in areas with high prevalence such as Sinjai Regency. This study aims to evaluate the implementation of stunting prevention and handling programs comprehensively, including the effectiveness of regional policies, inter-sector coordination, community participation, and the impact of the COVID-19 pandemic on the sustainability of the program. This study uses a qualitative approach with a case study design, supported by descriptive quantitative data through surveys and hypothesis tests on 5 key variables of the program. The results of the study show that the implementation of the program still faces various challenges. Qualitative findings show weak cross-sector coordination, low understanding of Regent Regulation No. 40 of 2021 regulations at the implementing level, limited training for posyandu cadres, and suboptimal child growth monitoring system. In addition, the survey results showed that public perception of program effectiveness was highest in the aspects of community participation (82%) and OPD coordination (78%), while cadre training (58%) and regulatory understanding (60%) obtained lower effectiveness scores. This shows the inequality between policy design and the reality of implementation on the ground. The impact of the COVID-19 pandemic has also been proven to worsen access to basic services, reduce exclusive breastfeeding coverage, and increase the risk of stunting in vulnerable groups. This study concludes that the optimization of stunting programs must be carried out through strengthening coordination across OPDs, integrating information systems, revitalizing cadre training, and active involvement of community leaders. A participatory approach based on local socio-cultural has proven to be effective in increasing public acceptance of government programs. The novelty of this research lies in an integrative approach that brings together policy evaluation, technical implementation, and social dynamics of the community in one analysis framework based on local context. These results are expected to be a reference in the formulation of stunting policies that are more adaptive and sustainable at the regional level.